Loneliness and Celluar Confinement in English Prisons 1878-1921 - Forsythe, Bill (The British journal of criminology, 2004)
This article aims to examine the practice of cellular confinement in English prisons between 1878 and 1921. In particular, I discuss the provenance of this feature of prison discipline before looking at the actual implementation of cellular confinement in the period under consideration. Some of the psychological effects on prisoners of this system are described, as well as some of the ways in which prisoners and staff sought to soften or evade its rigour